### view list-nat0.agda @ 790:1e7319868d77

Sets is CCC
author Shinji KONO Fri, 19 Apr 2019 23:42:19 +0900 d6a6dd305da2
line wrap: on
line source
```
module list-nat0 where

open import Level

postulate a : Set
postulate b : Set
postulate c : Set

infixr 40 _::_
data  List {a} (A : Set a) : Set a where
[] : List A
_::_ : A → List A → List A

infixl 30 _++_
-- _++_ : {a : Level } → {A : Set a} → List A → List A → List A
_++_ : ∀ {a} {A : Set a} → List A → List A → List A
[]        ++ ys = ys
(x :: xs) ++ ys = x :: (xs ++ ys)

l1 = a :: []
l2 = a :: b :: a :: c ::  []

l3 = l1 ++ l2

infixr 20  _==_

data _==_ {n} {A : Set n} :  List A → List A → Set n where
reflection  : {x : List A} → x == x
eq-cons : {x y : List A} { a : A } → x ==  y → ( a :: x ) == ( a :: y )
trans-list : {x y z : List A} { a : A } → x ==  y → y == z → x == z
--      eq-nil  : [] == []

list-id-l : { A : Set } → { x : List A} →  [] ++ x == x
list-id-l = reflection

list-id-r : { A : Set } → ( x : List A ) →  x ++ [] == x
list-id-r [] =   reflection
list-id-r (x :: xs) =  eq-cons ( list-id-r xs )

-- listAssoc : { A : Set } → { a b c : List A} →  ( ( a ++ b ) ++ c ) == ( a ++ ( b ++ c ) )
-- listAssoc   = eq-reflection

list-assoc : {A : Set } → ( xs ys zs : List A ) →
( ( xs ++ ys ) ++ zs ) == ( xs ++ ( ys ++ zs ) )
list-assoc  [] ys zs = reflection
list-assoc  (x :: xs)  ys zs = eq-cons ( list-assoc xs ys zs )

open  import  Relation.Binary.PropositionalEquality
open ≡-Reasoning

cong1 : ∀{a} {A : Set a } {b} { B : Set b } →
( f : A → B ) → {x : A } → {y : A} → x ≡ y → f x ≡ f y
cong1 f refl = refl

lemma11 :  ∀{n} →  ( Set n ) IsRelatedTo ( Set n )
lemma11  = relTo refl

lemma12 : {L : Set}  ( x : List L ) → x ++ x ≡ x ++ x
lemma12 x =  begin  x ++ x  ∎

++-assoc : {L : Set} ( xs ys zs : List L ) → (xs ++ ys) ++ zs  ≡ xs ++ (ys ++ zs)
++-assoc [] ys zs = -- {A : Set} →  -- let open ==-Reasoning A in
begin -- to prove ([] ++ ys) ++ zs  ≡ [] ++ (ys ++ zs)
( [] ++ ys ) ++ zs
≡⟨ refl ⟩
ys ++ zs
≡⟨ refl ⟩
[] ++ ( ys ++ zs )
∎

++-assoc (x :: xs) ys zs = -- {A : Set} → -- let open  ==-Reasoning A in
begin -- to prove ((x :: xs) ++ ys) ++ zs ≡ (x :: xs) ++ (ys ++ zs)
((x :: xs) ++ ys) ++ zs
≡⟨ refl ⟩
(x :: (xs ++ ys)) ++ zs
≡⟨ refl ⟩
x :: ((xs ++ ys) ++ zs)
≡⟨ cong1 (_::_ x) (++-assoc xs ys zs) ⟩
x :: (xs ++ (ys ++ zs))
≡⟨ refl ⟩
(x :: xs) ++ (ys ++ zs)
∎

--data Bool : Set where
--      true  : Bool
--      false : Bool

--postulate Obj : Set

--postulate Hom : Obj → Obj → Set

--postulate  id : { a : Obj } → Hom a a

--infixr 80 _○_
--postulate  _○_ : { a b c  : Obj } → Hom b c → Hom a b → Hom a c

-- postulate  axId1 : {a  b : Obj} → ( f : Hom a b ) → f == id ○ f
-- postulate  axId2 : {a  b : Obj} → ( f : Hom a b ) → f == f ○ id

--assoc : { a b c d : Obj } →
--    (f : Hom c d ) → (g : Hom b c) → (h : Hom a b) →
--    (f ○ g) ○ h == f ○ ( g ○ h)

--a = Set

-- ListObj : {A : Set} → List A
-- ListObj =  List Set

-- ListHom : ListObj → ListObj → Set

```